Karakteristik Fisikokimia dan Preferensi Cascara Terbuat dari Kulit Kopi Robusta var. Tugu Sari dan Bp 42 - N nurhayati (Politeknik Negeri Jember, 2020)
Coffee pulp is a potential source of antioxidants and phenolic compounds, so coffee pulp has the potential to be used as an ingredient a beverage. Cascara tea is a tea made from the pulp of Arabica and Robusta coffee. Information about the physicochemical characteristics and preferences of cascara tea made from Arabica, but until now there has been no information about the physicochemical and preferences from Robusta coffee. The content of phenolic compounds in coffee pulp originating from different plantations and varieties will vary, besides the processing also shows very different phenolic compounds and caffeine content. It is necessary to determine the effect of different varieties and pre-drying processes to determine physicochemical characteristics and consumer preferences for Robusta cascara tea drinks. This study used Completely Randomized Design (CRD) consisting of two factors, there were variety (A) and pre-drying process (B). Variety difference factor consists of two levels, namely A1 (Tugu Sari) and A2 (BP 42), while the pre-drying process consists of two levels, namely B1 (stripping before drying) and B2 (stripping after drying). Physicochemical data were analyzed using ANOVA (Î± = 5%) and continued using DMRT while preference data were analyzed using Chi-square test (Î± = 5%). Determination of the best treatment using qualitative descriptive with scoring analysis. The best treatment was Tugu Sari variety with stripping treatment before drying with overall preference value was preferred by panelists and total polyphenol value of 10.65 GAE / mL; antioxidant activity of 70,12%; caffeine level of 1,25%; total titrated acid of 2,57%; pH of 3,76; specific gravity of 1,042 mg / mL; total dissolved solids of 2 oBrix; brightness of (L *) 27,48